(untitled) (Comunicação & Inovação, 2017)
This text reflects on the human phenomenon of mimesis. We notice that encouraging the use of technological devices through aesthetic and marketing strategies walked along with the production of specific content, leading to the consumption of goods and services especially geared to children. We conclude that there are issues to consider by social agents on the excessive and unmonitored use of electronic devices by children. Our theoretical foundation considers the contribution of Christoph Wulf, Flusser and Norval Baitello Jr., among others.